What the World Needs Now is Jazz - Herzig, Monika (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
The worldwide lockdown caused by the COVID-19 pandemic initiated an economic crisis, especially in the performing arts world. With all events cancelled for many months and limited options to return to live performance in the future, the arts community had to respond quickly. The jazz model, specifically improvisational training, has been discussed frequently in entrepreneurship literature as a useful model for making decisions in uncertain situations. The principle of Effectual Entrepreneurship, defined as engaging in a continuous cycle of ideation and experimentation towards creating solutions from available means and techniques, is usually associated with a growth mindset fostered by training in improvisational techniques. This article documents how the directions and activities pursued by jazz musicians who train their improvisational capacities on a regular basis produce evolving new models of mediatized musical performance. Data collected from a survey, published literature, and several in-depth interviews and conclusions point towards a hybrid model of new technologies and modes of interaction combined with the need to preserve human engagement.